Religiusitas dan Ketidakjujuran Akademik pada Mahasiswa Kristen di Universitas Kristen di Tangerang - Anita Djie; Jessica Ariela (Indonesian Journal for The Psychology of Religion, 2021)
Academic dishonesty is a frequent problem in university and negatively impacts college students’ future. Therefore, this problem is necessary to be highlighted and solved. Prior studies had shown the importance of religiosity in the lives of college students. Students with high religiosity can remember and use their religious values to comprehend every university-related decision. By having high religiosity. Students can potentially apply their religious values as lifestyle and can have religious communities that can remind the students not to attempt things prohibited by their religion. Therefore, high religiosity should have been helpful to promote academic honesty. This study aimed to investigate whether there is a correlation between religiosity and academic dishonesty in 152 Christian students in a Christian university in Tangerang. This research was conducted using a quantitative method with The Four Basic Dimensions of Religiousness and Academic Dishonesty Scale as instruments of research. The result of the study showed that there was a significant negative correlation between religiosity and academic dishonesty (rs= -.200, p<.05). This finding showed that the higher the religiosity, the lower the academic dishonesty. Related additional analysis was also discussed.